Level-Based Clustering Approach to Scheduling Workflows in Clouds - Alrawashdeh, Tawfiq; Mohamad, Zarina; Hayati Zakaria, Aznida (International Journal of Engineering and Technology, 2018)
With the rapid increment on the complexity of the workflow, and the resultant demand on the scalability of the environment, executing workflows on traditional environment such as grids and clusters has become challenging task. Generally, schedulers aims to find a trade-off between execution, user requirement, and execution cost. Combine this with the uncertainty in the execution environment results in underlining the importance of designing scalable scheduling algorithm that adopt to the changes in the execution process. Toward this end, we propose the Level-Based Clustering (LBC) algorithm. By considering each level tasks as a single object (cluster), this algorithm aims to establish a relationship between the execution requirement for each cluster, and the number of resources that must be used to execute the entire workflow. We have compared our algorithm with three well-known algorithms from the literature, and the result show that the LBC algorithm achieves 50%, 25%, 50% on average improvement in term of cost, makespan and the number of resources used, respectively.Â Â
Keywords: scheduling; workflows; cluster; divide and conquer.